Tied up in knots - Sommer, Carl, 1930-; Budwine, Greg (Houston, TX : Advance Pub., 1997)
Until they see their two stubborn mules finally resolve a behavior problem, Benny and Sally refuse to believe that sharing could bring happiness.
Keywords: Sharing -- Fiction; Obstinacy -- Fiction; Behavior -- Fiction; Mules -- Fiction